FFA2 activation combined with ulcerogenic COX inhibition induces duodenal mucosal injury via the 5-HT pathway in rats - Akiba, Yasutada (Am J Physiol Gastrointest Liver Physiol, 2017)
Serotonin (5-HT), predominantly synthesized and released by enterochromaffin cells, is implicated in gastrointestinal symptoms such as emesis, abdominal pain, and diarrhea. Because luminal short-chain fatty acids (SCFAs) release 5-HT from enterochromaffin cells, which express the SCFA receptor free fatty acid receptor 2 (FFA2) in rat duodenum, we examined the effects of the selective FFA2 agonist phenylacetamide-1 (PA1) on duodenal 5-HT release with consequent bicarbonate secretion [duodenal bicarbonate secretion (DBS)] and on indomethacin (IND)-induced enteropathy. Intestinal injury was induced by IND (10 mg/kg sc) with or without PA1. We measured DBS in vivo in a duodenal loop perfused with PA1 while measuring 5-HT released in the portal vein. Duodenal blood flow was measured by laser-Doppler flowmetry. IND induced small intestinal ulcers with duodenal sparing. PA1 given with IND (IND + PA1) dose dependently induced duodenal erosions. IND + PA1-induced duodenal lesions were inhibited by the FFA2 antagonist GLPG-0974, ondansetron, or omeprazole but not by RS-23597 or atropine. Luminal perfusion of PA1 augmented DBS accompanied by increased portal blood 5-HT concentrations with approximately eight times more release at 0.1 mM than at 1 µM, with the effects inhibited by coperfusion of GLPG-0974. Luminal PA1 at 1 µM increased, but at 0.1 mM diminished, duodenal blood flow. Cosuperfusion of PA1 (0.1 mM) decreased acid-induced hyperemia, further reduced by IND pretreatment but restored by ondansetron. These results suggest that, although FFA2 activation enhances duodenal mucosal defenses, FFA2 overactivation during ulcerogenic cyclooxygenase inhibition may increase the vulnerability of the duodenal mucosa to gastric acid via excessive 5-HT release and 5-HT(3) receptor activation, implicated in foregut-related symptoms such as emesis and epigastralgia. NEW & NOTEWORTHY Luminal free fatty acid receptor 2 agonists stimulate enterochromaffin cells and release serotonin, which enhances mucosal defenses in rat duodenum. However, overdriving serotonin release with high luminal concentrations of free fatty acid 2 ligands such as short-chain fatty acids injures the mucosa by decreasing mucosal blood flow. These results are likely implicated in serotonin-related dyspeptic symptom generation because of small intestinal bacterial overgrowth, which is hypothesized to generate excess SCFAs in the foregut, overdriving serotonin release from enterochromaffin cells.